Simulation and Experimental Evaluation of a 5-Level Cascaded H-Bridge Inverter - Mahmud Ismaila; Sulaiman Haruna Sulaiman; Ibrahim Abdulwahab; Ibrahim Abdullahi Shehu; Musa Mohammed (Universitas Negeri Surabaya or The State University of Surabaya, 2025)
Multilevel inverters (MIs) are designed in such a way that different DC sources could be used to achieve the desired output voltage. This includes high quality output voltage, reduction of voltage stress on the switches, low common mode voltages, better harmonic content and reduction in total harmonic distortion compared to the conventional voltage source inverter. As there will be reduction in THD the size of the filter will also get minimized which decreases complexity of the system. Sinusoidal pulse width modulation technique is commonly employed in MIs in order to obtain undistorted output voltage by eliminating lower order harmonics. Cascaded H-bridge MIs are the most preferable for this purpose due to their modularity, reliability, less usage of clamping diodes and ease of control of circuitry and it also reduces the switching and conduction losses of the system. In this study, 5-level cascaded H-bridge inverter was simulated in MATLAB/Simulink software environment. A prototype of the simulated 5-level inverter was also constructed and the result was compared with that obtained from simulation. The results of both the simulation and experimental measurement have the similar output voltage waveform and the THD value of 33.12% and 33% for the simulation and experiment respectively.